State Companies as Claimants Under the 1965 Washington Convention on Investment Disputes Between States and Foreign Persons - N. S. Andreeva (Теоретическая и прикладная юриспруденция)
In this article, the author examines the status of state-owned companies as claimants under the 1965 Washington Convention on the settlement of investment disputes between States and nationals of other States and the competence of the International Centre for Settlement of Investment Disputes to consider claims of the stateowned companies. The paper considers possible limitations of the right of action of the state-owned companies, reﬂected in the so-called “Broches test”. As a result of the analysis of the case law of international investment tribunals the author concludes that the right of recourse to international investment arbitration shall in any case be available for the state-owned companies which perform a commercial function. In addition, the author proposes an algorithm for determining whether a state-owned company, which is authorized to exercise elements of state power, has the right of action.